Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies